Records of experiments in catering and dietary studies - Campbell, Stella; McNutt, Cora E. (My University, 1906)
Introduction: The following experiments were conducted between November 30th, 1905 and April 4th, 1906, for the purpose of ascertaining the amount of materials used, their composition, cost, fuel value expressed in calories, and nutritive ratios; also the amount of labor and time required in catering. The record is of six experiments: Number I. Football banquet given November 30th, 1905 to fifty persons. This was the first meal for the team after being for several weeks on rigid training diet. The materials were in season, therefore the prices were r reasonable. The work of preparation was done entirely by two women assisted in serving by seven others. Hours required for preparation 13-1/2, Hours required for serving 1-1/2, Total 15. Number II. A wedding luncheon given December 18th, 1905 to thirty-five persons. The prices of materials were reasonable taking into consideration that it was the beginning of the winter season. The work of preparation was done by two assisted in serving by six. Hours required for preparation 7, Hours required for serving 1, Total 8. Number III. A wedding dinner given January 17th, 1906 to twelve persons. Some materials being out of season made the cost greater than it would otherwise have been. Two prepared this dinner and one assisted in serving. Hours required for preparation 14, Hours required for serving 2, Total 16.
Citation: Campbell, Stella and McNutt, Cora E. Records of experiments in catering and dietary studies. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Catering; Dietary Studies; Home Economics; Theses